PENGARUH SOCIO DEMOGRAFI TERHADAP PENGETAHUAN IBU TENTANG KISTA BARTHOLINI DI PERUMAHAN BOLOASRI DESA BOLOREJO - siti mar maryam (ITKM WIDYA CIPTA HUSADA, 2020)
Bartholini cyst is a problem that is often found in women of reproductive age, most cases occur in the age range of 20 to 30 years with about 1 in 50 women will experience Bartholini cysts in their lives. This is an issue that needs attention and attention. Lack of information and social status of women in society is a major cause of reproductive health problems faced by women. In addition, women often ignore symptoms that are uncomfortable in the reproductive organs just because they are ashamed to have a check on their reproductive system disorders. This type of analytic research is observational approach, cross sectional time approach, sampling technique using purposive sampling, the number of samples is 36 respondents. The study was conducted from 20 to 27 May 2019 in the Boloasri Housing in Tulungagung Regency. The analysis used Chi Squar. Of the 36 respondents, almost half of the respondents were highly educated and had good knowledge, 15 (ρ <0.001), meaning there was an influence between education on knowledge. Most of the respondents were old (> 35 years old) and had good knowledge, 20 (ρ <0.01). influence between age on knowledge, Nearly half of respondents are workers and have good knowledge that is 14 (ρ <0.01) there is an influence between work on knowledge, almost half of respondents get information and have good knowledge that is 13 (ρ <0.03) which means there is an influence between information on knowledge, Almost half of respondents are of high economic status and have good knowledge which is 14 (ρ <0.05) which means there is an influence between economic status on knowledge. Facts and theories are in line that socio-demography is very influential on the knowledge of respondents For example, they will be more curious by attending training and seminars, so that they will increase the respondent's knowledge to be better related to bratholini cysts.